Adolescent Academic Resilience: The Role of Self-Regulated Learning and Optimism - Roosyiana, Dini Roosyiana; Niken Titi Pratitis; Mamang Efendy (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aims to examine the role of Self-Regulated Learning on Academic Resilience with Optimism as a mediating variable among adolescent students. The research was based on the importance of self-regulation and positive attitudes in coping with increasing academic demands. A quantitative approach using Structural Equation Modeling (SEM) with Confirmatory Factor Analysis (CFA) was applied to assess model fit and relationships among variables. The sample consisted of 430 junior high school students selected using a quota sampling technique based on grade level and gender. The results indicated that Self-Regulated Learning was significantly associated with Optimism (β = 0.496; p < .001) and Academic Resilience (β = 0.409; p < .001), while Optimism was also significantly associated with Academic Resilience (β = 0.197; p = .024). The indirect effect (β = 0.098; p = .021) revealed that Optimism partially mediated the relationship between Self-Regulated Learning and Academic Resilience. These findings highlight that the ability to self-regulate learning and maintain an optimistic mindset are closely associated with academic resilience among adolescents. The study suggests integrating reflective learning strategies and psychological support programs in schools to strengthen students' academic resilience.